Analysis of Musculoskeletal Disorder (MSDS) factors in production operator employees using the Quick Exposure Checklist (QEC) - Muflihat, Syakia; Ilmi, Nurul (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Production department operators perform repetitive work processes continuously, resulting in muscle and joint disorders. The purpose of this research is to identify early and provide preventive strategies for the potential occurrence of diseases due to musculoskeletal disorder complaints. (MSDs). This research is a qualitative study that involves direct observation of the subjects and interviews with sources to collect data using the Quick Exposure Check method. (QEC). The QEC results show that the wave solder workstation has the highest score with a total score of 141 and an exposure score of 80%. The cutting-point workstation has a score of 127 and an exposure score of 72%. The printing workstation has a score of 126 and an exposure score of 78%. The visual inspection workstation has a score of 107 and an exposure score of 61%. Therefore, the priority body parts are back with the highest total score of 30, the arms/shoulders with the highest total score of 36, and the wrists with the highest score of 40.